Las nenas terribles de Silvina Ocampo y Marosa di Giorgio - José Amícola (Cuadernos LIRICO)
The intention of the next pages is to draw attention to a new field of discussion on the Argentinean writer Silvina Ocampo’s literary works, focusing the analysis not only on the subject of class confrontation in her narrative but also on gender questions. We will consider the beginnings of three short stories, spanning three decades of her production -“Cielo de claraboyas” (1937), “El vestido de terciopelo” (1959) and “La muñeca” (1970)- where the narrative voice is that of a little girl. In opposition to this literary project, we will also study the Uruguayan writer Marosa di Giorgio’s literary work, who did not come from the high bourgeoisie like Silvina Ocampo but from a lower social class. Ironically, she had less to lose by risking positions on the subject of sexuality and could therefore show more freedom in the expression of desires.